Cyclic AMP-dependent signaling system is a primary metabolic target for non-thermal effect of microwaves on heart muscle hydration. (3rd April 2017) - Narinyan, Lilia; Ayrapetyan, Sinerik
ABSTRACT: Previously, we have suggested that cell hydration is a universal and extra-sensitive sensor for the structural changes of cell aqua medium caused by the impact of weak chemical and physical factors. The aim of present work is to elucidate the nature of the metabolic messenger through which physiological solution (PS) treated by non-thermal (NT) microwaves (MW) could modulate heart muscle hydration of rats. For this purpose, the effects of NT MW–treated PS on heart muscle hydration, [ 3 H]-ouabain binding with cell membrane, 45 Ca 2+ uptake and intracellular cyclic nucleotides contents in vivo and in vitro experiments were studied. It is shown that intraperitoneal injections of both Sham-treated PS and NT MW–treated PS elevate heart muscle hydration. However, the effect of NT MW–treated PS on muscle hydration is more pronounced than the effect of Sham-treated PS. In vitro experiments NT MW–treated PS has dehydration effect on muscle, which is not changed by decreasing Na + gradients on membrane. Intraperitoneal injection of Sham- and NT MW–treated PS containing 45 Ca 2+ have similar dehydration effect on muscle, while NT MW–treated PS has activation effect on Na + /Ca 2+ exchange in reverse mode. The intraperitoneal injection of NT MW–treated PS depresses [ 3 H]-ouabain binding with its high-affinity membrane receptors, elevates intracellular cAMP and decreases cGMP contents. Based on the obtained data, it is suggested that cAMP-dependent signaling system serves as a primary metabolic target for NT MW effect on heart muscle hydration.